Interactions between nesting crocodiles and iguanas (1981)
ABSTRACT: Green iguanas (Iguana iguana) and American crocodiles (Crocodylus acutus) nest in association on Slothia, a small island in Gatun Lake, Panama. In the three nesting seasons that we observed on Slothia a crocodile remained near her nest and frequently charged the nesting iguanas. Observations indicated that the crocodile emerged from the lake significantly more often when iguanas were present in the nest clearing. We observed the crocodile seize an iguana on 12 occasions; five iguanas were eaten, five escaped, and the fate of two was unknown. In addition to the charges and captures, the crocodile's mere presence in the nest clearing interfered with iguana nesting activity. Conversely, the iguanas disturbed the crocodile nest and were observed to dig up crocodile eggs. The crocodile's behavior involved both nest defense and predatory behavior, although the exact motivational sequence is still unclear. Crocodiles and iguanas share nest sites in several other locations near Slothia. Presumably, similar nest site requirements and common nesting seasons bring the two species together.